2010
DOI: 10.1182/blood-2009-08-237917
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles for LFA-1 affinity regulation during T-cell adhesion, diapedesis, and interstitial migration in lymph nodes

Abstract: During the course of homing to lymph nodes (LNs), T cells undergo a multistep adhesion cascade that culminates in a lymphocyte function-associated antigen 1 (LFA-1)-dependent firm adhesion to the luminal surface of high endothelial venules (HEVs). The importance of LFA-1 affinity regulation in supporting T-cell arrest on HEVs has been well established, however, its importance in the postadhesion phase, which involves intraluminal crawling and diapedesis to the extravascular space, remains elusive. Here we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
79
2
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 50 publications
(69 reference statements)
6
79
2
6
Order By: Relevance
“…34 It has been shown that genetically engineered T cells with affinity-enhancing LFA-1 mutation show perturbed intravascular crawling to transmigration sites, thereby compromising diapedesis across the blood vessels. 35 In our case, however, overexpression of TAGLN2 did not affect the migration of OTI CD8 + T cells into the tumor sites, suggesting that LFA-1 avidity regulation does not influence T-cell diapedesis across the tumor blood vessels. Moreover, we found that tumor non-specific polyclonal TG2P-CD8 + T cells have little effect on tumor suppression (data not shown), suggesting that the TAGLN2–actin–LFA-1 axis can be effective when T cells are activated via TCRs or CARs.…”
Section: Discussioncontrasting
confidence: 54%
“…34 It has been shown that genetically engineered T cells with affinity-enhancing LFA-1 mutation show perturbed intravascular crawling to transmigration sites, thereby compromising diapedesis across the blood vessels. 35 In our case, however, overexpression of TAGLN2 did not affect the migration of OTI CD8 + T cells into the tumor sites, suggesting that LFA-1 avidity regulation does not influence T-cell diapedesis across the tumor blood vessels. Moreover, we found that tumor non-specific polyclonal TG2P-CD8 + T cells have little effect on tumor suppression (data not shown), suggesting that the TAGLN2–actin–LFA-1 axis can be effective when T cells are activated via TCRs or CARs.…”
Section: Discussioncontrasting
confidence: 54%
“…Whereas the exact mechanism causing the hyperadhesiveness of the integrins is not known, the symptoms bear resemblance to mice expressing constitutively active LFA-1 in which excessive adhesion prevents leukocytes from entering injured tissues and, when tested in vitro, causes increased adhesion and stalled migration. [15][16] Insight into the mechanisms of glucocorticoid action might also help to explain the diminished recurrence of skin infections.…”
Section: Figurementioning
confidence: 99%
“…LFA-1 also supports monocyte firm adhesion and crawling in quiescent condition, whereas Mac-1 is responsible for TNF-a-stimulated monocyte crawling (16). Multiple functional states of LFA-1 with different affinities are required for lymphocyte rolling, adhesion, and crawling because no Mac-1 molecules are presented onto lymphocyte surface (17)(18)(19)(20). These observations bring up a question why the two structurally similar b 2 integrins behave distinctly in leukocyte recruitment and what the underlying mechanisms are.…”
mentioning
confidence: 99%
“…Although a body of evidences has been found to focus on the functional differences between Mac-1 and LFA-1 using in vivo, ex vivo, and in vitro measurements (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), it is still hard to provide a mechanistic insight. One way to elucidate the underlying mechanisms is to quantify the binding kinetics because it determines the on-and off-rates and binding affinity of interacting molecules.…”
mentioning
confidence: 99%